Solitary osteochondroma of the scapula: a rare case report - P, Rahul; TV, Ravikumar; Grover, Amit; K, Sudarshan (International Journal of Medicine, 2014)
Introduction: Osteochondroma is the most common benign bone tumor representing about 15 % of all bone tumors and 45.3 % of the benign bone tumors. They commonly arise from the metaphysis of a long bone with most common sites being distal femur, proximal tibia or proximal humerus. The occurrence of osteochondroma in flat bones particularly the scapula is uncommon. Case Presentation: In view of its rarity, we report a case of solitary osteochondroma of the scapula in an 18 year old male arising from the postero medial aspect of the body of scapula which was managed by excisional biopsy. He presented with a painless swelling of 2 years duration over the left scapula. Histopathology confirmed the diagnosis with no evidence of malignant transformation. Discussion: Osteochondromas are primary bone tumors rarely found arising from the scapula. Although the exact etiology of the growth is unclear, it is due to a portion of physis herniating through the growth plate. Complications like malignant transformation, winging of scapula and restriction of shoulder movements can occur. Thickness of cartilagenous cap is an important predictor of malignant change. Conclusion: Solitary osteochondroma of the scapula is a rare entity .Timely diagnosis and complete excision of the tumor should be done in order to avoid recurrence and prevent complications. Keywords: Osteochondroma, Solitary, Scapula.